The essence and content of labour-law principles of the legal regulatory framework for the National Police staffing in Ukraine - Harbuziuk, K. H.; Гарбузюк, К. Г.; ORCID: http://orcid.org/0000-0002-6714-5074 (Підприємництво, господарство і право. - 2022. - № 6. - С. 56-60, 2022)
Здійснено загальнотеоретичний аналіз поняття принципів та принципів права. Сформовано теоретико-концептуальну позицію щодо сутності принципів трудового права. Визначено зміст і сутність трудових принципів правового регулювання кадрового забезпечення Національної поліції України, а також проведено їх класифікацію. Встановлено, що важливими принципами правового регулювання кадрового забезпечення Національної поліції України є спеціальні трудоправові принципи, які притаманні виключно цьому напряму юридичного впливу, а не всій галузі трудового права. З-поміж зазначених принципів варто виділити такі: а) принцип стабільності (кадрове забезпечення здійснюється систематично та супроводжує весь трудовий процес усіх працівників Національної поліції України); б) принцип комплексності (кадрове забезпечення має не тільки виражатися в підготовці паперів для здійснення тих чи інших кадрових заходів, а й постійно відстежувати кадрові проблеми Національної поліції України та формувати шляхи їх вирішення); в) принцип пріоритету трудових інтересів поліцейських (кадрове забезпечення органів Національної поліції України має бути спрямоване насамперед на формування найбільш сприятливих умов для реалізації поліцейськими наданих і гарантованих їм Конституцією України та законодавством трудових прав, а вже потім кадрової політики керівництва); г) принцип розвитку кадрового потенціалу (кадрове забезпечення повинне спрямовуватися на постійне підвищення кваліфікації та професійних навичок кадрового складу поліції з метою поліпшення виконання поліцейськими своїх трудових і службових функцій, а також посилення вимог до кандидатів на службу в Національній поліції України).

The purpose of the article is to establish the essence and content the labour-law principles of the legal regulatory framework for the staffing of the National Police of Ukraine. The article, relying on the review of scientific perspectives, conducts a general theoretical analysis of the concept of principles and legal principles. A theoretical and conceptual perspective on the essence of the principles of labour law is formed. The content and essence of labour principles of the legal regulatory framework for the staffing of the National Police of Ukraine are determined and classified. It is established that important principles of the legal regulatory framework for the National Police of Ukraine staffing are special labour-law principles inherent exclusively in this area of legal influence, and not in the entire labour law. These principles include the following: a) the principle of stability (the staffing is systematic and accompanies the entire labour process of all employees of the National Police of Ukraine); b) the principle of comprehensiveness (the staffing should not be limited to the documental preparation of personnel actions, but also constantly monitor the personnel problems of the National Police of Ukraine and develop ways to solve them); c) the principle of the primacy of police officers’ labour interests (the staffing of the National Police of Ukraine should be aimed primarily at an enabling environment for the police officers provided and guaranteed to them by the Constitution of Ukraine and legislation on labour rights, and then at the personnel policy of the leadership); d) human capacity development principle (the staffing should be aimed at continuous development of the qualifications and professional skills of the police personnel with a view to improving the performance of duties and functions by the police; as well as strengthening the requirements for candidates to serve in the National Police of Ukraine). It is concluded that, to date, only a few of these principles have been incorporated into the legal framework governing the procedures for staffing the National Police of Ukraine. This reveals the inadequacy and ineffectiveness of the legal regulatory framework for the performance of police officers, as a result of which there is room for violation of their labour rights and the interests guaranteed by the Constitution and other labour legislation of Ukraine. We argue that one way of remedying this negative point is to legislate the system of principles proposed above in a separate, special document – the Law of Ukraine “On Police Performance”.

Проведен общетеоретический анализ понятия принципов и принципов права. Сформирована теоретико-концептуальная позиция относительно сущности принципов трудового права. Определены содержание и сущность трудовых принципов правового регулирования кадрового обеспечения Национальной полиции Украины, а также проведена их классификация.
Сутність та зміст трудоправових принципів правового регулювання кадрового забезпечення органів Національної поліції України
Harbuziuk, K. The essence and content of labour-law principles of the legal regulatory framework for the National Police staffing in Ukraine / Kostiantyn Harbuziuk // Підприємництво, господарство і право. - 2022. - № 6. - С. 56-60. - DOI: https://doi.org/10.32849/2663-5313/2022.6.08.
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; трудоправові принципи; labor law principles; трудоправовые принципы; кадрове забезпечення; personnel support; кадровое обеспечение; поліцейські; police officers; полицейские; принципи права; principles of law; принципы права; правове регулювання; legal regulation; правовое регулирование